2013
DOI: 10.5121/ijcnc.2013.5112
|View full text |Cite
|
Sign up to set email alerts
|

A User Profile Based Access Control Model and Architecture

Abstract: Personalization and adaptation to the user profile capability are the hottest issues to ensure ambient assisted living and context awareness in nowadays environments. With the growing healthcare and wellbeing context aware applications, modeling security policies becomes an important issue in the design of future access control models. This requires rich semantics using ontology modeling for the management of services provided to dependant people. However, current access control models remain unsuitable due to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
(5 reference statements)
0
5
0
1
Order By: Relevance
“…These proposals should then guide the elaboration of models for extensive trace-driven simulations so that numerical observations could therefore be obtained; (ii) to study live streaming on the Internet to evaluate the eventual changes or adaptations that should occur in BitTorrent's peer selection and piece selection policies, respectively. This would certainly help the design of novel BitTorrent-like protocols targeted at the requirements of live streaming services [1,29]; lastly, to analyse the influences of the personalization and adaptation to the client´s capability profile as well as of the Network Address Translation (NAT) service on the design of P2P streaming protocols [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…These proposals should then guide the elaboration of models for extensive trace-driven simulations so that numerical observations could therefore be obtained; (ii) to study live streaming on the Internet to evaluate the eventual changes or adaptations that should occur in BitTorrent's peer selection and piece selection policies, respectively. This would certainly help the design of novel BitTorrent-like protocols targeted at the requirements of live streaming services [1,29]; lastly, to analyse the influences of the personalization and adaptation to the client´s capability profile as well as of the Network Address Translation (NAT) service on the design of P2P streaming protocols [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the increased HR is considered as critical for a speci c patient in case that his healthcare situation, his activity levels or his age are taken into account. Zerkouk et al [30] suggested an adaptable access control paradigm and its related architecture, where the security policy is based on an analysis of the user's monitored behavior. Røstad et al [31] introduced a mechanism for personalized access control in health records.…”
Section: Manasa Et Almentioning
confidence: 99%
“…In (Sujansky et al, 2010), the authors have described the design and implementation of an access-control mechanism for PHR repositories, that is modeled on the eXtensible Access Control Markup Language (XACML) standard. (Zerkouk et al, 2013) have presented a novel adaptable access control model and its related architecture. The security policy is based on the handicap situation analyzed from the monitoring of user's behavior, in order to grant a service using any assistive device within intelligent environment.…”
Section: Background and Literature Related To Access Controlmentioning
confidence: 99%